Memahami Fenomena Quiet Quitting sebagai Akomodasi Komunikasi dalam Pengalaman Bekerja di Kalangan Generasi-Z - Hafyan Syafi Baihaqi; Yohanes Thianika Budiarsa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The phenomenon of quiet quitting has gained significant attention in the modern workplace, particularly among Generation Z employees who possess distinct work characteristics and expectations compared to previous generations. This study aims to understand how Generation Z interprets quiet quitting as a form of communication accommodation in their work experiences. The research employs an interpretive paradigm with a qualitative phenomenological approach. Data were collected through in-depth interviews with three Generation Z informants who had work experience and demonstrated characteristics associated with quiet quitting behavior. Data were analyzed using Creswell’s phenomenological approach, which draws on Moustakas’ framework. The analysis involved horizontalization, clustering of themes, the construction of textual and structural descriptions, and the synthesis of the essence of participants’ lived experiences.. The findings reveal that quiet quitting is perceived as a communication strategy to maintain personal boundaries, mental well-being, and work-life balance. Experiences of limited openness in communication, lack of appreciation, restricted opportunities for participation, and imbalanced communication between supervisors and employees encouraged participants to reduce emotional involvement and contributions beyond their formal responsibilities. From the perspective of Communication Accommodation Theory, this behavior can be understood as a form of divergence communication manifested through limited participation and emotional withdrawal from the organization. The study concludes that quiet quitting should not merely be viewed as a lack of work commitment, but rather as a communication response emerging from individuals’ subjective experiences within the workplace.